Unfolding the privacy paradox among mobile social commerce users: a multi-mediation approach. Issue 6 (3rd June 2018) - Ooi, Keng-Boon; Hew, Jun-Jie; Lin, Binshan
ABSTRACT: Considering that privacy paradox is currently an underexplored research area, this study proposes a privacy paradox model to explain the reasons behind such phenomenon. Built upon the theoretical link of belief-intention-behaviour and the idea of multi-mediation, this study seeks to discover the relationship between concern for social media information privacy and usage intention, and the potential mediators that stand between such linkage. The results suggest that perceived mobility and social support do mediate the said linkage, and the model could reasonably explain usage intention, which surprisingly has a negative association with usage behaviour. Theoretical and practical implications are subsequently offered.